Pertanggungjawaban Hukum terhadap Kecelakaan Kapal dalam Perspektif Teori Hukum - Faozaro Nduru; Aartje Tehupeiori; Wiwik Sri Widiarty (Syntax Idea)
The purpose of this study is to analyze and describe the responsibility of insurance parties for ship accidents at sea that provide legal certainty and justice; and to analyze and describe the legal protection and legal certainty provided by the insurance against ships2 that have accidents at sea. The type of research used is normative juridical Doctrinal legal research which is conceptualized as statutory rules, and doctrinal legal research which is conceptualized based on judges' decisions. Because normative legal research examines literature and library materials, there are also those who classify normative legal research as literature research. Insurance liability for ship accidents at sea is very important to provide legal certainty and justice for all parties involved. This requires legal certainty so that all parties know their respective rights and obligations, and justice to ensure that all parties get fair treatment according to the losses they have suffered. To protect the rights and interests of each party, the insurance provides legal protection and legal certainty for ships that have accidents at sea. With legal protection and certainty, the problems of the parties involved in ship accidents will be easier to resolve fairly